Analysis of US Scan findings in neonates with increased risk factors for Developmental Dysplasia of the Hip (DDH) - Gamage, M.A.M.N.; Rupasinghe, D. (Proceedings of the Scientific Sessions 2016, FMS, USJP in collaboration with SJGH, 2016)
Attached

Objectives: To analyse US Scan abnormalities detected in neonates with increased risk factors for DDH Methods: Descriptive analysis of the US Scan reports and Bed Head tickets were done using a Per forma in 100 neonates detected to have increased risk factors for DDH. Results: There were 52 female babies in our study and all were bom at term. The indications for hip US scans were breech presentation in 56% and detection of a unilateral ‘hip click’ in 42%. Out of all requested, only 96 attended for Us scan assessment. Thirty one babies were detected to have shallow acetabulum during the initial assessment while repeat scan done after 6 weeks showed that only 4 babies needed an orthopaedic referral. Twenty four babies found to have shallow acetabulum and aU babies who needed orthopaedic referral were screened ultrasonically due to a Hip ‘Click’ detected during neonatal check. ’onclusions: Careful Clinical hip screening is very important and can use as a guide to decide need for H itf ^ 3